Perancangan Konten Sosial Media Wisata Agro Lembah Kecubung - Syafiq Rizal Widiananta (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This research aims to design an effective social media content strategy to promote Kecubung Valley Agro Tourism. Agro-tourism is increasingly popular as a recreational destination, and social media has become a crucial platform for introducing and promoting tourism destinations. The study involved an in-depth analysis of agrotourism characteristics and target audience preferences. Through a content design approach that focuses on visuals, narrative and interaction, this research seeks to create an interesting experience for social media users. The research methodology includes surveys, interviews and analysis of social media data related to similar destinations. The results are expected to provide insight into user preferences, social media content trends, and the best strategies to increase the visibility of Lembah Agro Tourism. This research contributes to a practical understanding of how to design social media content that can increase user attraction and interaction, thereby advancing the promotion and marketing of agro-tourism destinations.